Intestinal parasitosis and socio-environmental factor sof a population from peri-urban area of Manaus - AM - Cecília Leite Motta de Oliveira; William Antunes Ferreira; Felicien Gonçalves Vasquez; Maria das Graças Vale Barbosa (Universidade de Fortaleza, 2010)
Objectives: To describe the prevalence of intestinal parasitosis in patients who sought a Basic Health Unit and get to know the conditions and socio-environmental characteristics of a population of peri-urban area of Manaus - AM, Brazil. Methods: A study conducted by spontaneous demand of patients in a Basic Health Unit, Northern Zone of Manaus, Amazonas, between April and July 2007, conducting parasitological examination in 400 stool samples by Hoffmann-Pons-Janer's method, and interviews. Results: From the total, 271/400 (67,8%) contained parasites; 181/268 (45,25%) samples were of females; 147/224 (36,7%) aged between 19 and 85 years; 119/170 (29,75%) with incomplete elementary school; 207/299 (51.75%) with a family income between one and three minimum wages; 220/316 (55%) were natural from Amazonas; 192/284 (48%) worked at home; 199/298 (49,7%) consumed water from artesian public well; 106/152 (26.5%) treated the water; 165/248 (66%) did not treat the consumed water. The most frequent helminthes found: Ascaris lumbricoides 48 (12%), Enterobius vermicularis 44 (11%), Ancilostomídeos 38 (9,5%). Protozoa: Entamoeba histolytica 83 (20,8%), Entamoeba coli and Endolimax nana, 79 (19,8%) e 79 (19,8%) respectively, Giardia lamblia 41 (10,3%) and Iodamoeba butschlii 17 (4,3%). It was observed monoparasitism for E. histolytica 83 (20,8%), biparasitism 104/271 (26%) E. histolytica and A. lumbricóides, E. histolytica and E. vermicularis, E. histolytica and G. lamblia. Conclusions:   We recorded a high prevalence of parasites in young people with low income, low cultural level, predominantly women of the household. Among the environmental factors associated with these indexes are a deficiency in water services and sanitary sewer.